Clinical efficacy of triamcinolone acetonide and Ranibizumab in the treatment of diabetic diffuse macular edema - Bi-Hua Xie (Guoji Yanke Zazhi, 2018)
AIM:To compare the clinical curative effect of triamcinolone acetonide and Ranibizumab on diffuse diabetic macular edema(DME). METHODS: We collected 84 cases of patients with diffuse DME treated in our hospital from February 2016 to May 2017. According to 1:1 matching method, they were divided into Ⅰ, Ⅱ groups. They were all treated with laser photocoagulation. Preoperative auxiliary application of triamcinolone acetonide was given to Group Ⅰ, while Group Ⅱ received preoperative application of ranibizumab. After treatment, the efficacy of the two groups were analyzed and compared. RESULTS: The total clinical efficiency of Group Ⅱ at 3mo after treatment was 93%, higher than that of Group Ⅰ(77%; χ2=4.981, P=0.025). Compared with before treatment, BCVA and CMT of the two groups at each time after treatment were significantly improved(P<0.05). BCVA of Group Ⅱ at 1 and 3mo after treatment was better than that of Group Ⅰ(P<0.05); CMT of Group Ⅱ at 1, 3 and 6mo after treatment improved more than that of Group Ⅰ, with significant difference(P<0.05); occurrence rate of adverse reactions Group Ⅰ and Group Ⅱ were 17% and 13% with no significant statistical difference(χ2=0.243, P=0.621). There were no serious adverse reactions such as retinal detachment, endophthalmitis or cataract in the two groups. CONCLUSION: Compared with triamcinolone acetonide, the effect of ranibizumab on diffuse diabetic macular edema is better, and has high clinical value.